Setting Up Joint Ventures in China - Devonshire-Ellis, Chris; Scott, Andy.; Woollard, Sam.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This brand new guide book is a comprehensive overview of establishing joint ventures in China. It details all applicable decision making processes such as assessing your potential partner, choosing the relevant JV structure, conducting legal and financial due diligence. The guide contains complete JV contract and articles of association as well as an overview of JV law, details negotiation issues, land use rights, IP Protection and technology transfer, in addition to tips on staff hiring and HR. It also describes the tax and audit responsibilities in addition to buying out a JV partner and liquidations. It is a concise, detailed yet pragmatic guide of use to anyone considering or owning a JV in China.
Assessing the Need For a Chinese Partner -- JVs vs. WFOEs -- China$1 (Bs JV Implementation Laws -- Equity and Co-operative JVs -- Legal and Financial Due Diligence -- Memorandums of Understanding -- Key Points in JV Negotiations -- Encouraged Industry Applications -- Development Zones and Tax Incentives -- JV Contracts and the Articles of Association -- Land Use Rights -- Protecting Your IP -- Technology Transfer Agreements -- Human Resources and Acquiring Staff -- Taxes and Audit Requirements -- Repatriating Profits -- Converting a JV To a WFOE -- Buying Out Your JV Partner -- Liquidating a JV.s
Keywords: Economics; Industrial management; Entrepreneurship; Economics/Management Science; Management/Business for Professionals; Entrepreneurship